Principles and practice of mechanical ventilation - Tobin, Martin J. (McGraw-Hill Medical, 2006)
Presents the account of the use of mechanical ventilation in critically ill patients. This title features coverage that addresses important scientific, clinical, and technical aspects of the field as well as chapters that encompass the full scope of mechanical ventilation, including the physical basis of mechanical ventilation.